2021
DOI: 10.9734/sajrm/2021/v9i130199
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Methanolic Extract for Antimicrobial Activity of Hyphaene thebaica L. Fruit Pulp from Sudanese Folklore

Abstract: Aim: To evaluate the antimicrobial potential of the methanolic extract of the fruit pulp of Hyphaene thebaica (Doum), a famous natural product in Sudan. Methods: Agar-well diffusion test and minimum inhibition diffusion test (MIC). Results: The investigation revealed that the extract showed no antifungal effect against Aspergillus niger ATCC 6275 and Candida albicans ATCC 10231. While it exhibited remarkable antibacterial activity against Staphylococcus aureus ATCC BAA 1026 and Pseudomonas aerugino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Meanwhile, Behiry et al [65] found that the methanolic extract from banana peels at concentrations of 1, 2, and 3% inhibited the mycelial growth of Fusarium culmorum and Rhizoctonia solani fungi. Even though all concentrations of methanolic doum extract had slight antifungal properties, Taha et al [66] and Abdallah [67] reported that the doum methanolic extract exhibited no antifungal activity against A. flavus and A. niger ATCC 6275. It has been reported that the existence of alkaloids, tannins, phenolics, cardiac glycosides, saponin, and flavonoids in different fruit peel extracts has been correlated with antifungal activity [63,68].…”
Section: Effect Of the Applied Plant Extracts On A Flavus Growth And Afb1 Productionmentioning
confidence: 99%
“…Meanwhile, Behiry et al [65] found that the methanolic extract from banana peels at concentrations of 1, 2, and 3% inhibited the mycelial growth of Fusarium culmorum and Rhizoctonia solani fungi. Even though all concentrations of methanolic doum extract had slight antifungal properties, Taha et al [66] and Abdallah [67] reported that the doum methanolic extract exhibited no antifungal activity against A. flavus and A. niger ATCC 6275. It has been reported that the existence of alkaloids, tannins, phenolics, cardiac glycosides, saponin, and flavonoids in different fruit peel extracts has been correlated with antifungal activity [63,68].…”
Section: Effect Of the Applied Plant Extracts On A Flavus Growth And Afb1 Productionmentioning
confidence: 99%
“…The pathogenic foodborne and spoilage molds tested in this study differed in their sensitivity to the methanolic extract of Doum, wherein Bacillus cereus and C. albicans, and S. aureus were the most sensitive indicators followed by T. mentagrophyte and E. coli, respectively, while no effect was noticed against Aspergillus flavus. Antimicrobial activity (Figure 3 and Table 3) of Doum extract against B. cereus, C. albicans, S. aureus, T. mentagrophyte, and E. coli were 29, 27, 25 mm 23, and 13 mm, respectively, when compared with the traditional antibiotics, with minimal lethal concentrations (Table 3) ranged of 32, 32, 64, 64 and 128 mg/ml, respectively, these results were different comparing with what obtained by Abdallah [68]. While the methanolic extract of Carob exhibited a weak antibacterial effect (20 mm) only against B. cereus, with minimal lethal concentration of 128 mg/ml and no effect observed against the other tested pathogens.…”
Section: Antimicrobial Activity Of Both Doum and Carob Methanolic Ext...mentioning
confidence: 64%
“…These results were confirmed by MIC and MBC tests ( 22 . Our previous study showed that doum extract was active against an American type culture collection strain of Staphylococcus aureus (ATCC BAA 1026) 8 , where recorded 16.0 mm inhibition zone and 62.5 MIC. Meaning that, this beta-lactamase Staphylococcus aureus is much susceptible to the doum methanolic extract.…”
Section: Resultsmentioning
confidence: 99%
“…Sudan and Egypt are both familiar with the local name "Doum". Palms of doum are cultivated in the northern, southern, and western regions of Sudan 8,9 . Doum fruit has good nutritional and pharmaceutical properties, according to literature; it contains carbohydrates, fibers, essential minerals, some vitamins, and good amounts of phenolic compounds, all of which are important in controlling various physiological processes in the human body and protection against oxidation stresses, inflammations, microbes and cancer 10,11 .…”
Section: Introductionmentioning
confidence: 99%